Environmental Gains of Precision Agriculture in Brazilian Soybean Production: A Life Cycle Assessment Approach - , Marcelo Corrêa da Silva; , Clandio Favarini Ruviaro (Archives of Current Research International, 2025)
Aims: As a global leader in soybean production, Brazil faces intensifying environmental challenges driven by conventional agricultural practices. This underscores the need for sustainable intensification strategies. Study Design: This study employed Life Cycle Assessment (LCA) to compare the environmental performance of soybean cultivation under precision agriculture (PA)-based fertility management with conventional systems. Place and Duration of Study: Conducted in Mato Grosso do Sul over a five-year period (2019–2023). Methodology: The analysis used a cradle-to-farm gate approach, with 1 kg of soybean grain as the functional unit. Primary data were collected from a commercial farm utilizing PA, while benchmark data from Embrapa represented the conventional system. Environmental impacts were assessed in four categories: global warming potential (GWP), acidification potential (AP), eutrophication potential (EP), and human toxicity potential (HTP). Monte Carlo simulations and sensitivity analyses ensured result robustness. Results: PA significantly reduced environmental impacts: −60.84% (EP), −31.79% (AP), −28.65% (GWP), and −19.54% (HTP). The planting and fertilization stages were the primary contributors to overall impacts. Conclusion: The findings highlight PA as a promising strategy for sustainable intensification, improving environmental outcomes and resource efficiency. However, adoption remains limited due to high upfront costs and technical knowledge requirements. These insights reinforce the policy relevance of promoting PA through incentives, training, and infrastructure, and demonstrate its potential scalability across similar production systems.